Smart Farming: Future of Agriculture - T. Geetha Jebarathnam Kuttibai; M. S. Bhagavathi; V. Prakash (Research Highlights in Agricultural Sciences Vol. 6, 2022)
World Food production need to be increased by 70% during 2050 as stated by the UN Food and Agriculture Organization, owing to the shrinking land resources and the tremendous growth of the world population exponentially. Despite the fact, the scarce availability of fresh water and arable land ,migration of agriculture workforce, linked with declined yield trends had further pushed too far the problem. Ratification of super highway in agriculture had been a head start to combat the declining agricultural workforce. Agriculture has undergone many revolutions, regardless of the domestication of plants and animals, way back a millennium ago, standardized adoption like rotations of crop, other farming practices a few years ago or the applications of technologies like plant breeding and organics for yield escalation and pest and weed control a decennial ago ,the green revolution. In the dawn of the new millennium, the thrust in agriculture, is undergoing a fourth revolution triggered by the opportunity of exponentially escalating use of information and communication technology (ICT).